Design of an Archimedes' spiral based node deployment scheme targeting enhancement of network lifetime in wireless sensor networks. (January 2015) - Halder, Subir; Das Bit, Sipra
Abstract: Wireless sensor networks (WSNs) have been receiving significant attention due to their potential applications in environmental monitoring and surveillance domains. In WSNs, unbalanced energy consumption is an intrinsic problem and this can considerably decrease network lifetime. One primary way of mitigating uneven energy consumption is judicious deployment of sensor nodes so that the energy flow remains balanced throughout the network. In this work, at first we analyze layered network architecture and find out the conditions that need to be satisfied for optimal deployment setting in order to achieve complete area coverage, energy balance and prolonged network lifetime. We also analyze two standard distribution functions to find out their suitability as node deployment function and found neither of the distribution functions ensures balanced energy consumption, thereby failing to prolong network lifetime. Keeping the conditions of optimal node deployment setting in mind, and considering the reasons of unsuitability of the two standard distributions mentioned above, we identify Archimedes' spiral based on which a node deployment function is proposed. Furthermore, we show the proposed deployment function provides optimal deployment setting and derive the constraint for balanced energy consumption, thereby subsequent enhancement of network lifetime. Exhaustive simulation is performed primarily to measure the extent of achieving our design goal of enhancing network lifetime while attaining energy balancing and maintaining coverage. We also measure the effect of placement errors on the performance of the scheme and show that even in presence of placement error the performance is comparable with the other competing schemes. Further, the simulation results show that our scheme does not compromise with other network performance metrics such as end-to-end delay and throughput while achieving the design goal. Finally, all the results are compared with three competing schemes and the results confirm our scheme's supremacy in terms of both design performance metrics as well as network performance metrics. Graphical abstract: Nodes are to be deployed along the turns at discrete points staring from next to sink position as shown in figure to achieve energy balancing as well as enhancement of network lifetime of WSNs. Highlights: Node deployment scheme targeting enhancement of network lifetime in WSNs. Identify conditions for optimal deployment setting in layered network architecture. Identify Archimedes' spiral, based on which a node deployment function is proposed. Shown that the proposed deployment scheme provides optimal deployment setting.